Islamic Economics in The Dynamics of Digital Transformation and Financial Inclusion: A Narrative Literature Reviewrticle Title Review - Lia Anggita Putri (PT. Samudra Solusi Profesional, 2024)
Islamic economics has experienced significant growth over the past two decades, particularly in Muslim-majority countries such as Indonesia. This development is reflected in the expansion of Islamic banking, the strengthening of Islamic social finance instruments such as zakat and waqf, and the emergence of digital-based innovations including Islamic fintech and digital Islamic banking services. Despite this progress, numerous studies indicate that the contribution of Islamic economics to national economic development remains constrained by structural challenges, including low levels of Islamic financial literacy, limited Islamic financial inclusion, and a persistent gap between the normative ideals of Sharia principles and their practical implementation. This article aims to analyze the development, challenges, and opportunities of Islamic economics in the contemporary context by employing a qualitative approach using a narrative literature review method. Data were obtained from national and international peer-reviewed journal articles, academic books, and official reports issued by institutions such as Statistics Indonesia (BPS), the Financial Services Authority (OJK), and Bank Indonesia. The analysis applies thematic content analysis to identify dominant themes and patterns within the literature. The findings indicate that digital transformation holds substantial potential to enhance Islamic financial inclusion and improve the efficiency of Islamic financial and social finance institutions. However, the effectiveness of digitalization is highly dependent on strengthening Islamic financial literacy, improving governance and regulatory frameworks, and ensuring consistent implementation of maqashid al-sharia principles. This article contributes conceptually by providing a comprehensive thematic mapping of Islamic economics literature and offers practical insights for policymakers and stakeholders involved in the development of Islamic economic ecosystems in Indonesia